2005
DOI: 10.1016/j.virusres.2005.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral expression of a truncated S1 subunit of SARS-CoV spike protein results in specific humoral immune responses against SARS-CoV in rats

Abstract: The causative agent of severe acute respiratory syndrome (SARS) has been identified as SARS-associated coronavirus (SARS-CoV), but the prophylactic treatment of SARS-CoV is still under investigation. We constructed a recombinant adenovirus containing a truncated N-terminal fragment of the SARS-CoV Spike (S) gene (from--45 to 1469, designated Ad-S(N)), which encoded a truncated S protein (490 amino-acid residues, a part of 672 amino-acid S1 subunit), and investigated whether this construct could induce effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 44 publications
1
57
0
Order By: Relevance
“…A number of studies have shown that S protein and its fragments induce SARS-CoV-neutralizing antibodies [16,[24][25][26][27][28][29][30][31][32][33]. The receptor-binding domain (RBD) in the S1 region plays a critical role in the neutralizing antibody induction as well as ACE2 binding and viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that S protein and its fragments induce SARS-CoV-neutralizing antibodies [16,[24][25][26][27][28][29][30][31][32][33]. The receptor-binding domain (RBD) in the S1 region plays a critical role in the neutralizing antibody induction as well as ACE2 binding and viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…Several vaccine strategies proposed for prevention of SARS include inactivated virus-based vaccines (15), DNA-based vaccines (16), recombinant subunit vaccines (17), and viral vector-based vaccines (18). These vaccine candidates are able to induce protective immune responses against SARS-CoV, including NA and T cell immune responses (14, 19 -21).…”
Section: Intranasal Vaccination Of Recombinant Adeno-associated Virusmentioning
confidence: 99%
“…Recombinant Ad5 (E1/E3 -)-based vectors encoding ␤-galactosidase (Ad/LacZ) and human interferon-␥ (Ad/IFN-␥) were constructed as previously reported (Huang and Flint, 1998;Liu et al, 2005;L. Li et al, 2006;X.…”
Section: Cell Lines and Recombinant Adenoviral Vectorsmentioning
confidence: 99%